PTSD symptoms, suicidality and non-suicidal risk to life behavior in a mixed sample of pre- and post-9/11 veterans. Issue 5 (2nd September 2016) - Barr, Nicholas Upton; Sullivan, Kathrine; Kintzle, Sara; Castro, Carl Andrew
ABSTRACT: This study investigated relationships between symptom clusters of posttraumatic stress disorder (PTSD), suicidal ideation, suicide plan, and non-suicidal risk to life behavior (NSRB) behavior in a sample of 1, 356 pre- and post-9/11-era military veterans. After controlling for a positive PTSD screen, results indicated that suicidal ideation was significantly associated with re-experiencing symptoms ( OR = 1.12), White race (OR = 1.82) and use of pain medication (COR = 1.62). Suicide plan was associated with avoidance symptoms ( OR = 1.08), and NSRB with hyperarousal symptoms ( OR = 1.11) and severe alcohol use ( OR = 2.10). Standardized coefficients indicated that re-experiencing symptoms ( b = .38) were a stronger predictor of suicidal ideation than White race ( b = .16) or pain medication ( b = .12) and that hyperarousal symptoms ( b = .36) were a stronger predictor of NSRB than severe alcohol use ( b = .15). The interpersonal–psychological theory of suicide was used to frame a discussion of military specific suicide risk as well as the risk of premature death among veterans who endorse NSRB but not suicidality. We suggest that this subset of veterans may be overlooked by traditional screening methods while nonetheless presenting with great risk for premature death.